The effect of the Common Agricultural Policy reforms on intentions towards food production: Evidence from livestock farmers. (January 2016) - Barnes, Andrew; Sutherland, Lee-Ann; Toma, Luiza; Matthews, Keith; Thomson, Steven
Highlights: Responses to previous policy reform is a strong predictor of future intentions. The majority of farmers seek no changes in their business up to 2020. Decrease in subsidies will have a greater effect than an increase in payment. Path dependency should be explored further in intentions studies. Abstract: Reform of the EU Common Agricultural Policy (CAP) contributes to uncertainty in farm planning and a number of studies have examined farmer intentions to possible future support scenarios. This paper extends this literature by examining the effect of past reform on influencing farmer intentions towards the most recent reform of the CAP. Agricultural production-related intentions up to 2020 are assessed for a survey of 1764 livestock based holdings in Scotland. The influence of the Fischler reform is estimated, in addition to a hypothetical payment increase and a payment decrease scenario for the new reforms. The majority of farmers stated a desire to remain on the same trajectory under both business as usual and payment increase scenarios. Under a payment decrease scenario, the number of farmers stating they would exit the industry more than doubled from 4% to 9% and around half the respondents stated they would decrease both herd size and intensity if payments were to decrease. Consequently, this may be some evidence of a loss aversion effect. Response to past reform was found to be a significant predictor of intention to change as well as the identification of a successor within the farm household. This alludes to the path dependency model of transition within agriculture and these factors as possible triggers of change within the farm. We propose that future studies of farmer intentions should include some of these temporally distinct variables to explain change.